2002
DOI: 10.2486/indhealth.40.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Activity of Erythrocyte Pyrimidine 5'-Nucleotidase (P5N) in Lead Exposed Workers: With Focus on the Effect on Hemoglobin.

Abstract: Anemia that accompanies lead poisoning is in part the result of various inhibitory effects of lead on heme biosynthesis. Lead also increases the rate of red blood cell destruction due to the profoundly depressed activities of erythrocyte pyrimidine 5'-nucleotidase (P5N) activities. We studied parameters of the two metabolic pathways in the workers exposed to lead to evaluate P5N in the lead exposed workers and which pathway has an effect on hemoglobin (Hb) level. 29 male workers in the secondary lead smelting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Historically, molecular toxicity was believed to be caused by the displacement of Zn 2+ or Ca 2+ by Pb 2+ ions, and various studies have since demonstrated that Pb 2+ can occupy binding sites for many physiologically essential metals, including: Mg 2+ in pyrimidine 5'-nucleotidase type 1 (135); Zn 2+ in 5-aminolevulinic acid dehydratase (ALAD) (136, 137), resulting in iron deficiency associated with anaemia; and Fe 2+ in divalent metal transporter-1 (DMT1), which appears to be involved in transport and uptake of Pb 2+ (138, 139). The Pb 2+ ion can also occupy Ca 2+ -binding sites, and/or displace Ca 2+ in many proteins, including voltage-gated calcium channels (VGCCs) (140), troponin C (98), CaM (32), PKC (58), parvalbumin (64), and synaptotagmin (40).…”
Section: A New Perspective For the Molecular Basis Of Pb2+ Toxicitymentioning
confidence: 99%
“…Historically, molecular toxicity was believed to be caused by the displacement of Zn 2+ or Ca 2+ by Pb 2+ ions, and various studies have since demonstrated that Pb 2+ can occupy binding sites for many physiologically essential metals, including: Mg 2+ in pyrimidine 5'-nucleotidase type 1 (135); Zn 2+ in 5-aminolevulinic acid dehydratase (ALAD) (136, 137), resulting in iron deficiency associated with anaemia; and Fe 2+ in divalent metal transporter-1 (DMT1), which appears to be involved in transport and uptake of Pb 2+ (138, 139). The Pb 2+ ion can also occupy Ca 2+ -binding sites, and/or displace Ca 2+ in many proteins, including voltage-gated calcium channels (VGCCs) (140), troponin C (98), CaM (32), PKC (58), parvalbumin (64), and synaptotagmin (40).…”
Section: A New Perspective For the Molecular Basis Of Pb2+ Toxicitymentioning
confidence: 99%
“…Pb 2+ has been found to displace Mg 2+ in pyrimidine 5'-nucleotidase type 1 [13], inhibiting the activity of the enzyme. This decreased activity results in increased concentrations of pyrimidines with an increased rate of destruction of red blood cells leading to anemia [14]. Pb 2+ has also been shown to replace Zn 2+ in 5-aminolevulinic acid dehydratase (ALAD) [15, 16], an important enzyme in heme synthesis, resulting in iron-deficiency anemia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that at lower concentrations, Pb 2+ induces CaM activity while inhibiting the same at higher concentrations . Although the Pb 2+ binding site is not as explicitly defined as the EF-hand motif, several studies demonstrated that Pb 2+ binding to a variety of proteins affects their conformations, causing functional impairment. …”
Section: Discussionmentioning
confidence: 99%